The voice of children who live with HIV on implications of the disease in their daily life - Kuyava, Joel; Rubim Pedro, Eva Neri (Investigación y Educación en Enfermería, 2014)
Objective. To determine the effects of HIV/AIDS on the daily lives of HIV-infected children, based on their responses to a semistructured interview. Methods. This exploratory descriptive study with a qualitative approach was carried out from November 2012 to March 2013 among five children with HIV aged 11 to 12 years. The children were registered at the non-governmental organization “Mais Criança” in Porto Alegre/RS/Brazil. Data were collected using semi-structured interviews, and the results were submitted to thematic analysis. Results. The analysis of content identified two categories: fears in daily life of the child with HIV and experiences: lived knowledge. With regard to daily life, the children reported no difference in their lives compared with the lives of other children because they can take part in any activities they want if they are taking their medicines. They seemed to have positive expectations about the future. Conclusion. Children with HIV/AIDS live in a complex situation with severe conflicts. However, their childhood is similar to that of other children without the disease. Health professionals, especially nurses, need to develop strategies to strengthen the bond with these children and their families in order to give them the opportunity to express their feelings and to cope better with living with the disease.